The Younger Dryas age of the Salpausselkä moraines in Finland - J. Donner (Bulletin of the Geological Society of Finland, 2010)
The late-glacial Younger Dryas Stadial, as defined over seventy years ago in Denmark, was compared with the withdrawal of the Scandinavian ice sheet and correlated in Finland in 1951 with the formation of the Salpausselkä moraines. Since then a great number of studies of Younger Dryas has eventually led to its definition in the Event Stratigraphy for the North Atlantic region, based on the oxygen isotope stratigraphy in the Greenland ice-core NGRIP. The age of the Younger Dryas/Preboreal boundary, the beginning of the Holocene, is in this stratigraphy dated at 11653 yr. BP, an age close to the age deter-mined for the drainage of the Baltic Ice Lake and the beginning of the rapid retreat of the ice margin from Salpausselkä II in Finland and the corresponding Billingen moraine in Sweden. This leads to the conclusion that the Salpausselkä moraines Ss I and Ss II were formed during Younger Dryas, according to the revised varve chronology between c. 12 260 and c. 11600 yr. BP. The third Salpausselkä, Ss III, was according to this dating formed in early Holocene. After the 1950s, when the Salpausselkä moraines were dated as having been formed during the Younger Dryas Stadial, the ages of the boundaries of Younger Dryas changed as a result of revisions of the time scales of varved clays and the use of radiocarbon ages and their calibrations. As a result of these changes the age of the two main Salpausselkä moraines, Ss I and Ss II, is older than assumed 60 years ago on the basis of the varve chronology.